2018
DOI: 10.22190/fupes171103043r
|View full text |Cite
|
Sign up to set email alerts
|

Preschool Sport Management: The Role of Basic Sports in Preschools

Abstract: Basic sports management in preschools is an area on which, in the region of Southeast Europe, no country has particularly focused. Investing in preschool sports organization is necessary for several reasons: The first reason is to raise the level of the nation's health. The second reason relates to the prevention of illness in later life, and the third reason is the possibility of creating future athletes, or making a home base from which the most talented children would be directed to local clubs in sports in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Gallahue, Ozmun & Goodway (2011) thinks that physical activity positively affects fundamental movement patterns and encourages learning the sports technique of performing some elements. Furthermore, attending institutions in early childhood such as kindergarten (Sabo, 2003(Sabo, , 2004Venetsanou & Kambas, 2010), recreational and sports clubs (Radošević, Gavrilović, Veselinović, & Parčina, 2018;Temple, Crane, Brown, Williams, & Bell, 2016), and family indoor and outdoor activities (Barnett, Hinkley, Okely, & Salmon, 2013) have a positive impact on child motor learning and development. Temple et al (2016) have found that the more active categories of physical activities, active recreation and organized sports predict at least one subtype of motor skill in preschool children.…”
Section: Introductionmentioning
confidence: 99%
“…Gallahue, Ozmun & Goodway (2011) thinks that physical activity positively affects fundamental movement patterns and encourages learning the sports technique of performing some elements. Furthermore, attending institutions in early childhood such as kindergarten (Sabo, 2003(Sabo, , 2004Venetsanou & Kambas, 2010), recreational and sports clubs (Radošević, Gavrilović, Veselinović, & Parčina, 2018;Temple, Crane, Brown, Williams, & Bell, 2016), and family indoor and outdoor activities (Barnett, Hinkley, Okely, & Salmon, 2013) have a positive impact on child motor learning and development. Temple et al (2016) have found that the more active categories of physical activities, active recreation and organized sports predict at least one subtype of motor skill in preschool children.…”
Section: Introductionmentioning
confidence: 99%